2021
DOI: 10.1186/s12978-021-01223-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sanitary pad distribution and reproductive health education on upper primary school attendance and reproductive health knowledge and attitudes in Kenya: a cluster randomized controlled trial

Abstract: Background Adolescent girls’ risk of school dropout and reproductive health (RH) challenges may be exacerbated by girls’ attitudes toward their bodies and inability to manage their menstruation. We assessed effects of sanitary pad distribution and RH education on girls in primary grade 7 in Kilifi, Kenya. Methods A cluster randomized controlled trial design was used. Eligible clusters were all non-boarding schools in three sub-counties in Kilifi Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 27 publications
(34 reference statements)
0
49
0
Order By: Relevance
“…(2) knowledge of biological facts about menstruation (which are important, for example, in shaping knowledge and practices to prevent adolescent pregnancies) (24,59); (3) knowledge about MHM (which is important in supporting girls' broader health and access to education) (47,60); and (4) the ability to apply this new knowledge to local realities (including through efforts to provide local supplies and infrastructure that are supportive of MHM) (38,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) knowledge of biological facts about menstruation (which are important, for example, in shaping knowledge and practices to prevent adolescent pregnancies) (24,59); (3) knowledge about MHM (which is important in supporting girls' broader health and access to education) (47,60); and (4) the ability to apply this new knowledge to local realities (including through efforts to provide local supplies and infrastructure that are supportive of MHM) (38,51).…”
Section: Discussionmentioning
confidence: 99%
“…Although RCTs are less common, a cRCT in Kenya explored the impact on knowledge and attitudes of participating in reproductive health education classes over 25 sessions, delivered by trained facilitators during girls-only health clubs. The authors find that girls who participated felt more positively about menstruation, knew more about sexual and reproductive health, had more equitable gender norms, and were more self-confident by the end of the classes than those who did not Austrian et al (59). However, the intervention did not engage with the wider community to address drivers of poor knowledge or discriminatory gender norms.…”
Section: Gender-transformative Approaches and Interventions To Improv...mentioning
confidence: 97%
“…Previous studies have examined psychosocial outcomes and MHH as a way to measure effectiveness of MHH programming ( 62 , 63 ), in particular measuring self-efficacy using existing self-efficacy scales ( 33 , 47 , 64 ). Results from our study support the hypothesis that increasing MHH literacy significantly improves girls' menstruation-related stress and self-efficacy, though not school engagement ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the impacts of MHH education on school attendance have yielded mixed results ( 33 38 ), with different countries and programs demonstrating varying levels of absenteeism ( 39 41 ) and coping strategies among menstruating girls ( 42 ). Alternatively, in qualitative studies, girls consistently elaborate on the struggles of managing their periods at school.…”
Section: Introductionmentioning
confidence: 99%
“…11 Some studies have shown, however, that provision of products is not enough to significantly improve school attendance among girls. 12 13 Furthermore, although these policies represent an important step in support of gender equality, such policies are usually limited to the provision of period pads, with no menstrual education for girls or boys, often because of deeply rooted myths and taboos that code menstruation as bad, unclean, and to be hidden. 14 A further dimension for education and policy involves environmental waste, which will increase with greater access to disposable pads.…”
mentioning
confidence: 99%